(untitled) (Sains Humanika, 2018)
The aim of this study is to develop a better understanding of well-being concept as it relates to the children at Gaya Island. This study also focuses on quality of relationships of the children with others and their link with children’s happiness with life. Data for this study were obtained from 223 children with age ranged from 10 to 12 year old in the only one primary school at Gaya Island, Sabah. The Good Childhood Index was used to measure overall well-being and in relation to 10 aspects of the life of children. It includes a single-item measure of happiness with life as a whole, a five-item measure of overall life satisfaction. The results indicated that children in Gaya Island tend to be happy - the mean score on 10 point scale was 8.18. Around 7% of the children scored below the mid-point on this scale or around 16 out of 223 young people were more unhappy than happy. For life satisfaction scale, the score can range from 5 to 25. Again the result showed the life satisfaction of the children at Gaya Island was generally positive. The mean score on this scale was 19.22. Around 2.7% of children at Gaya Island scored below the mid-point of 15 on this scale. The result indicated that the choices in life and health condition were positive predictors of children’s happiness. Findings also showed well-being factors; relationship with family, choices in life, and appearance were significant predictors of Gaya Island’s children life satisfaction.